Modifiers of (CAG)(n) instability in Machado-Joseph disease (MJD/SCA3) transmissions: an association study with DNA replication, repair and recombination genes. - Martins, S (2014)
Twelve neurological disorders are caused by gene-specific CAG/CTG repeat expansions that are highly unstable upon transmission to offspring. This intergenerational repeat instability is clinically relevant since disease onset, progression and severity are associated with repeat size. Studies of model organisms revealed the involvement of some DNA replication and repair genes in the process of repeat instability, however, little is known about their role in patients. Here, we used an association study to search for genetic modifiers of (CAG)n instability in 137 parent-child transmissions in Machado-Joseph disease (MJD/SCA3). With the hypothesis that variants in genes involved in DNA replication, repair or recombination might alter the MJD CAG instability patterns, we screened 768 SNPs from 93 of these genes. We found a variant in ERCC6 (rs2228528) associated with an expansion bias of MJD alleles. When using a gene-gene interaction model, the allele combination G-A (rs4140804-rs2972388) of RPA3-CDK7 is also associated with MJD instability in a direction-dependent manner. Interestingly, the transcription-coupled repair factor ERCC6 (aka CSB), the single-strand binding protein RPA, and the CDK7 kinase part of the TFIIH transcription repair complex, have all been linked to transcription-coupled repair. This is the first study performed in patient samples to implicate specific modifiers of CAG instability in humans. In summary, we found variants in three transcription-coupled repair genes associated with the MJD mutation that points to distinct mechanisms of (CAG)n instability.